Model of Arabic Authentic Assessment Instruments: Speaking (Kalām) at Madrasah Aliyah - Raswan Raswan; N. Lalah Alawiyah; Taufik Luthfi (Jurnal Alsinatuna, 2022)
Authentic assessment is a model for assessing learning processes and outcomes that differ from ordinary assessments. Authentic judgment must be done in a natural context, not contrived, applied and taught. Authentic assessment is also an assessment mandate in Indonesia's latest curriculum, namely the 2013 Revised Curriculum (revised K.13). The speaking aspect is at the core of successfully learning other aspects of Arabic language skills: listening (istimā'), reading (qirā'ah), writing (kitābah) and culture (Ṡaqafah). With proper speaking assessment will be the capital of success in learning speaking and other aspects of learning Arabic. Therefore, a, this article aims to present an authentic assessment instrument model of aspects of Arabic speaking learning (kalām) based on revision K.13. The research method used is research on the development of 4D models, define (definition), design (Design), develop (Development) and disseminate (trial). The results showed that the speech skills assessment instrument developed in this article has good validity, through expert tests (84%) and public tests (78%). The results of this study state that the developed speech ability assessment instrument is suitable for use.